Implementasi Kurikulum Merdeka: Meningkatkan Sistem Pendidikan Indonesia? - Prada Destina Rahmadani; Diny Honggo Jati; Elia Ayu Pratama (AGUSPATI RESEARCH INSTITUTA, 2024)
The aim of this study is to determine the importance of implementing the independent curriculum. This study report uses a descriptive qualitative method by listening and taking notes because the source of the information was obtained from one of the YouTube channels of the Directorate of Primary Schools entitled